Bottom side‐roll feeding by humpback whales (Megaptera novaeangliae) in the southern Gulf of Maine, U.S.A. Issue 2 (24th July 2013) - Ware, Colin; Wiley, David N.; Friedlaender, Ari S.; Weinrich, Mason; Hazen, Elliott L.; Bocconcelli, Alessandro; Parks, Susan E.; Stimpert, Alison K.; Thompson, Mike A.; Abernathy, Kyler
Abstract Humpback whales (Megaptera novaeangliae) are known for the variety and complexity of their feeding behaviors. Here we report on the use of synchronous motion and acoustic recording tags (DTAGs) to provide the first detailed kinematic descriptions of humpback whales using bottom side‐rolls (BSRs) to feed along the seafloor. We recorded 3, 505 events from 19 animals (individual range 8–722). By animal, mean BSR duration ranged from 14.1 s to 36.2 s.; mean body roll angle from 80º to 121º, and mean pitch from 7º to 38º. The median interval between sequential BSRs, by animal, ranged from 24.0 s to 63.6 s and animals tended to maintain a consistent BSR heading during long BSR series encompassing multiple dives. BSRs were most frequent between 2200 and 0400. We identify three classes of behavior: simple side‐roll, side‐roll inversion, and repetitive scooping. Results indicate that BSR feeding is a common technique in the study area and there is both coordination and noncoordination between animals. We argue that this behavior is not lunge feeding as normally characterized, because animals are moving slowly through the event. The behavior also leads to vulnerability to entanglement in bottom‐set fishing gear, a major mortality factor for the species.